A design process for developing agricultural life science‐focused model eliciting activities. (29th December 2020) - Bostic, Jonathan D.; Clark, Quintana M.; Vo, Tina; Esters, Levon T.; Knoblach, Neil A.
Abstract: Agricultural life science topics include but are not limited to (1) agriculture and the environment, (2) culture, society, and economy, and (3) energy. These topics have potential to come up during mathematics and science instruction and offer learning opportunities. One way for agricultural life science topics to be part of such instruction is through tasks that encourage problem solving. Model‐eliciting activities (MEAs) are tasks that promote problem solving, draw upon real‐life experiences, and have potential to engage in learning across multiple disciplines. The purpose of this manuscript is to describe a qualitative, exploratory multiple case study. It answers the research question: What are important design features when developing Agricultural Life Science MEAs? Results from this study provide a viable roadmap as an approach to develop MEAs that address Agricultural Life Science issues. This roadmap includes six stages: problem identification, assessing developmental readiness, identifying potential engagement in the MEA, considering pedagogical supports, practitioner reviews, and finally field testing.